J/ψ production in pp̄ collisions at √s = 1.8 TeV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Álvarez, G; Alves, G; et al. (1996)
We have studied J/ψ production in pp̄ collisions at √s = 1.8 TeV with the DØ detector at Fermilab using μ+/μ- data. We have measured the inclusive J/ψ production cross section as a function of J/ψ transverse momentum, pT. For the kinematic range pT > 8 GeV/c and |η\ < 0.6 we obtain σ(pp̄ → J/ψ + X) ·Br(J/ψ → μ+μ-) = 2.08 ± 0.17(stat) ± 0.46(syst) nb. Using the muon impact parameter we have estimated the fraction of J/ψ mesons coming from B meson decays to be fb = 0.35 ± 0.09(stat)±0.10(syst) and inferred the inclusive b production cross section. From the information on the event topology the fraction of nonisolated J/ψ events has been measured to be fnonisol = 0.64 ± 0.08(stat)±0.06(syst). We have also obtained the fraction of J/ψ events resulting from radiative decays of χc states, fχ = 0.32 ± 0.07(stat)±0.07(syst). We discuss the implications of our measurements for charmonium production processes.